Reformasi Birokrasi Melalui Inovasi Sistem Informasi Aparatur Sipil Negara (SIASN) - N, Muhammad Iqbal; Hasanuddin; Auradian Marta (Jurnal Niara, 2024)
Bureaucratic reform at the State Civil Service Agency Regional Office apparatus. This research aims to determine the effectiveness of implementation and inhibiting factors in the implementation of bureaucratic reform through state civil service information system innovation (SIASN) at BKN Regional Office XII Pekanbaru. This research uses the Theory of Effectiveness Aspects of Bureaucratic Reform in government organizations by looking at Institutional Aspects, Bureaucratic Position Holders, Simplification of Management (Innovation), Human Resources, and Technical Capabilities. Location The research was carried out at BKN Regional Office XII Pekanbaru. This research uses a qualitative descriptive approach. Meanwhile, data collection techniques are carried out through interviews and documentation. Based on the research results, the author assesses that the implementation of Bureaucratic Reform through Innovation of the State Civil Apparatus Information System (SIASN) at the BKN Regional Office and are not used to using digital platforms so that the use of services in reforming Bureaucratic Reform through State Civil Apparatus Information System Innovation (SIASN) at BKN Regional Office XII Pekanbaru has not been maximized. The author assesses the need for system sustainability, development and comprehensive data integration in bureaucratic reform through SIASN "State Civil Apparatus Information System" at the State Civil Service Agency.